Analysis of swing movement in ballroom dancing - Shioya, T. (Proceedings, 2018)
Natural rise and fall movement represents typical characteristics of the swing dances in ballroom dances. The rise and fall movements are analyzed in the mechanical point of view in the presentation. The biomechanics of the rise and fall movements were analyzed in terms of the potential energy and the velocity of the body. Some basic figures of Waltz are taken as examples with application suggestion to the other dances. A sinusoidal function is employed for vertical and horizontal movements in the analysis featuring the natural swing movement of the dancer`s body. The height of center of gravity of dancer and its vertical acceleration are quantitatively exhibited in graphs for each basic movement of the figures of these dances. It is shown that the maximum height in the movement depends on each figure in each dance and that it is limited by the acceleration analysis regardless of dancer`s height or weight.